Potential value of rubber seed - Udomsakdhi B; Munsakul S; Sthapitanonda
Calculations based on the total area of rubber cultivated (4 609 276 rai, where 1 rai=0.16 ha) indicate a large yearly production of rubber seed (230 434 t). Only a small fraction of seed has been commecially exploited for oil and meal. Various potential uses of rubber seed are outlined.
Keywords: Commercial uses; Rubber seed meal; Rubber seed oil